INCREASE OF MECHANICAL FEATURES OF SECONDARY SILUMIN AK5M2 - Skujbida, O. L.; Volchok, I. P. (Science and Transport Progress, 2010)
The effect of refining-modifying treatment of secondary aluminum alloy АК5М2 was researched. The modifier 10…20 % Na2CO3, 15…20 % SrCO3, 12…20 % SiC, 3…8 % Ti, 0,5…2 % C, the rest S was worked out and used. The improvement of tensile strength and plasticity of the alloy was obtained.